39AR-40AR AGE AND PETROLOGY OF CHICO: LARGE-SCALE IMPACT MELTING ON THE L CHONDRITE PARENT BODY - Bogard D.D.; Garrison D.H.; Norman M.; Scott E.R.D.; Keil K. (My University, 1995)
Our studies of the 105 kg Chico L chondrite show that it contains #60% impact melt and the largest volume of impact melt recognized in stony meteorites. We suggest that it is part of a much larger dike complex that formed when chondritic impact melt was intruded into host chondrite during a large, if not catastrophic, impact on the L chondrite parent body at about 0.5 Ga. Petrologic and 39Ar-40Ar dating studies were made on several lithologies, including the massive melt zone, host chondrite, and melt-chondrite boundaries, for the purpose of studying the melting and thermal histories associated with impacts on small bodies and their effects on the K-Ar chronometer. The chondritic host is shocked to stage S6 and contains pockets and veins of melt. There are no unmelted clasts in the interior of the melt; coalesced metal-troilite nodules reach up to 2 cm in size. Melt near the contact with the host chondrite contains numerous clasts and quenched more rapidly. Metal-troilite textures suggest cooling rates of #0.1°C/s in the interior of the melt dike during crystallization. Secondary kamacite rims indicate cooling at 0.01 - 1°C/y over the range of 700-500°C, consistent with an impact-heated volume of up to a kilometer in thickness. Compositions of olivines and pyroxenes are generally similar in melt and chondritic host, reflecting rapid crystallization, not metamorphic equilibration. The interior melt shows an overall depletion in K, whereas the melt near the boundary is enriched in K. The 39Ar-40Ar release spectra during stepwise heating of both melt and chondrite samples can be divided into two parts, based on Ar diffusion properties and K ratios. The low-temperature, high K phase of both melt and host chondrite show ages of 0.54-0.78 Ga. Ages of the high-temperature, low K phase of the melt are comparable or higher, 0.61-1.35 Ga, whereas those of the host chondrite are even higher, 0.87-1.86 Ga, due to lesser degrees of degassing. Isochron plots for several melt samples suggest an age of #0.53 Ga and the presence of variable amounts of excess 40Ar not completely degassed by the impact. Even this age, however, is significantly higher than the previously reported Rb-Sr isochron age of 0.467 +/- .015 Ga. The apparent retention of radiogenic 40Ar in the Chico impact melt, in spite of its relatively large size, absence of clasts, and moderately slow cooling rate below 700°C, raises questions as to the reliability of using melts for 39Ar-40Ar dating of meteoritic impact events.